2019
DOI: 10.29399/npa.23654
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Childhood Trauma and Obsessive-Compulsive Disorder, Comorbid Attention Deficit Hyperactivity Disorder, and Impulsivity v

Abstract: Introduction: A growing body of research associates childhood trauma with obsessive-compulsive disorder (OCD). The aim of this study was to investigate the relationships between childhood trauma and OCD, including both its severity and OCD patients' comorbid impulsivity, ADHD, anxiety, and depressive symptoms. Methods: A convenient sample consisting of 106 patients with OCD was given the Childhood Trauma Questionnaire (CTQ), Yale-Brown Obsessive Compulsive Scale (Y-BOCS), Wender Utah Rating Scale (WURS), Hamil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Sensitivity analyses revealed that the total heterogeneity of the meta-analysis was reduced when removing the study of Semiz et al ( 34 ) or Coban et al ( 36 ), with the I 2 reduced to 0 and 37%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity analyses revealed that the total heterogeneity of the meta-analysis was reduced when removing the study of Semiz et al ( 34 ) or Coban et al ( 36 ), with the I 2 reduced to 0 and 37%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown a relation between childhood traumas and the severity of anxiety [4], depression [5], psychosis [6] and bipolar disorder [7]. Likewise, a recent study has shown a relation between childhood traumas and the severity of OCD symptoms, the occurrence of comorbid anxiety, increased impulsivity, increased incidence of attention deficit hyperactivity disorder (ADHD) and a lower educational level [8]. Even though fear of COVID-19 infection may not be fully comparable with the above mentioned traumas in childhood, it has been suggested that both depression, anxiety disorders, post-traumatic stress disorder, psychotic disorders and suicide may by consequences of fear of COVID-19, where individuals, who previously have experienced psychological disorders, may be specially prone [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a relation between childhood traumas and the severity of anxiety [4], depression [5], psychosis [6] and bipolar disorder [7]. Likewise, a recent study has shown a relation between childhood traumas and the severity of OCD symptoms, the occurrence of comorbid anxiety, increased impulsivity, increased incidence of attention de cit hyperactivity disorder (ADHD) and a lower educational level [8]. Even though fear of COVID-19 infection may not be fully comparable with the above mentioned traumas in childhood, it has been suggested that both depression, anxiety disorders, post-traumatic stress disorder, psychotic disorders and suicide may by consequences of fear of COVID-19, where individuals, who previously have experienced psychological disorders, may be specially prone [9].…”
Section: Introductionmentioning
confidence: 99%